Dark Side of the Moon: The Corruption of Communication in Influencer Marketing - Shela Nawanti Putri (Jobmark: Journal of Branding and Marketing Communication, 2021)
The rapid development of communication in the digital era is followed by the communication process in society. Digital communication media is considered efficient, practical and economical in delivering and receiving messages that can be completed quickly from one hemisphere to another. With the advancement of mobile technology, penetration of higher internet speeds, new marketing tools, and changing market trends, digital marketing is now considered as an alternative future, whose existence is gradually shifting other marketing methods, one of which is with influencers. AL is one of the influencers who use their followers on social media to promote branded products that want to collaborate. This collaboration is in the form of product reviews on Instagram social media that benefit him and the brand. One of the products that AL uses as an influencer to promote its products is SW. In this article, the researcher identifies acts of AL’s communication corruption based on the communication corruption theory.